PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI PERMAINAN ENGKLEK DI PAUD TERPADU ANANDA SIAK HULU KABUPATEN KAMPAR - ', Ermawati; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study are as follows: 1) To determine whether the hopscotch game can improve gross motor skills of 5-6 year old children in early childhood Integrated Ananda Siak Hulu Kampar Kampar regency. 2) To find out how the teachers in improving the gross motor skills of 5-6 year old children through early childhood game of hopscotch in Integrated Ananda Siak Hulu Kampar 3) To know how much Upgrades gross motor skills of 5-6 year old children through play hopscotch Integrated early childhood Ananda in Kampar Regency Siak Hulu. The subjects were PAUD Integrated Ananda Siak Hulu Kampar numbering as many children as 15 children, consisting of 7 men and 8 women. Collecting data using observation and documentation. The survey results revealed prasiklus obtained an average percentage of 45.0%. While the value of the first cycle to 55.8%. and the second cycle subsequent increase to the value of 84.2%. In testing the hypothesis can be seen an increase in earned on each cycle. Where an increase in gross motor skills obtained prior to action for the first cycle increased by 27.0%. While the increase in gross motor skills from the first cycle to cycle II of 33.5%, and the overall increase in gross motor skills of children from prasiklus to cycle II of 50.5%.Keywords: Rough motor skills, engklek games